Does the diversity of vegetation and diatoms correlate with soil and water factors in a tropical cloud forest’s complex land use/land cover scenario? - Vázquez, Gabriela; García-Franco, José G.; Castillo-Campos, Gonzalo; Martínez, M. Luisa; Mehltreter, Klaus; Campos, Adolfo; Favila, Mario E. (Environmental monitoring and assessment, 2024)
Soil and water characteristics in micro basins with different land uses/land cover (LULC) can influence riparian vegetation diversity, stream water quality, and benthic diatom diversity. We analyzed 18 streams in the upper part of the La Antigua River basin, México, surrounded by cloud forests, livestock pastures, and coffee plantations. Concentrations of P, C, and N were elevated in the humus of forested streams compared to other land uses. In contrast, cations, ammonium, and total suspended solids (TSS) of water streams were higher in pastures and coffee plantations. These results indicate that LULC affects stream chemistry differently across land uses. Vegetation richness was highest (86–133 spp.) in forest streams and lowest in pastures (46–102), whereas pasture streams had the greatest richness of diatoms (9–24), likely due to higher light and temperatures. Some soil and water characteristics correlated with both true diversity and taxonomic diversity; soil carbon exchange capacity (CEC) correlated with vegetation diversity ( r = 0.60), while water temperature correlated negatively ( r =  − 0.68). Diatom diversity was related to soil aluminum ( r =  − 0.59), magnesium ( r = 0.57), water phosphorus ( r = 0.88), and chlorophyll ( r = 0.75). These findings suggest that land use affects riparian vegetation, while physical and chemical changes influence diatom diversity in stream water and soil. The lack of correlation between vegetation and diatom diversity indicates that one cannot predict the other. This research is an essential first step in understanding how land use changes impact vegetation and diatom diversity in mountain landscapes, providing valuable insights for environmental monitoring and conservation efforts in tropical cloud forests.